Web Accessibility in Latin American Universities: A Path to Global Rankings and Digital Inclusion - Patricia Acosta-Vargas; Gloria Acosta-Vargas; Belen Salvador-Acosta; Marcos Chacon-Castro; Jadán Guerrero, Janio (My University, 2025)
Web accessibility is increasingly recognized as a key factor in assessing higher education institutions’ quality, inclusion, and social responsibility. This topic is particularly relevant in Latin America, where significant disparities in digital equity and access to resources persist. This study analyzes the web accessibility of the top 20 Latin American universities based on their rankings in QS World University Rankings, Webometrics, SCImago Institutions Rankings, and Times Higher Education (THE). Using automated and manual assessment tools, including WAVE, PageSpeed ​​​​Insights, and expert assessments, the study identifies 434 contrast errors, 210 missing text alternatives, and 262 navigation issues on university websites. The results show that universities such as USP, UNAM, and Unicamp rank high in international rankings but have critical accessibility deficiencies, highlighting the gap between digital visibility and inclusion. By aligning with WCAG 2.2 and the Sustainable Development Goals (SDGs), in particular SDG 4 (Quality Education), SDG 9 (Industry and Innovation), and SDG 10 (Reduced Inequalities), universities can improve global competitiveness while fostering digital inclusion. This research proposes a structured framework to promote accessibility through a seven-phase methodology, addressing barriers, implementing improvements, and validating effectiveness. The findings provide a systematic approach for universities to optimize accessibility, improve user experience, and strengthen their international positioning
Keywords: Latin American Universities; Sustainable Development Goals; Web Accessibility